THE ROLE OF THE NEWSPAPER “KHOREZM HAQIQATI” IN COVERING THE HOME FRONT LIFE OF THE PEOPLE OF KHOREZM (TAMADDUN NURI JURNALI, 2025)
The article presents materials on the issues of covering the details of the life of Khorezm people behind the front lines by analyzing articles in the newspaper “Khorezm haqiqati”.